Implementasi Pengembangan Kurikulum Madrasah Bertaraf Internasional - Shobri, Muwafiqus; Amaliyah, Indah Ratul (AKSI: Jurnal Manajemen Pendidikan Islam, 2022)
This paper is the result of a field study conducted at one of the educational institutions on the island of Bawean, namely Madrasah Aliyah Mambaul Falah Tambilung. The focus studied in this research is on how to implement the development of an international standard madrasa curriculum (MBI). This study aims to determine the implementation of international standard madrasa curriculum development. The research method used in this study is a qualitative method, while the data collection techniques used are observation, in-depth interviews, and documentation. The data analysis technique used is data reduction, data presentation, data conclusion. Checking the validity of the data used is source triangulation. The results of this study indicate that the implementation of the MBI curriculum development is carried out by a). Reviewing the curriculum by inviting lecturers and kiai from Java to review learning at MBI, b). Shaping the character of students starting from the beginning of school entry, and c) Focusing on deepening the subjects used for college entrance selection.